Cost effectiveness of patient education for the prevention of falls in hospital: economic evaluation from a randomized controlled trial - Haines, T.; Hill, A.; Hill, Keith; Brauer, S.; Hoffman, T.; Etherton-Beer, C.; McPhail, S. (BioMed Central Ltd., 2013)
Background: Falls are one of the most frequently occurring adverse events that impact upon the recovery of older hospital inpatients. Falls can threaten both immediate and longer-term health and independence. There is need to identify cost-effective means for preventing falls in hospitals. Hospital-based falls prevention interventions tested in randomized trials have not yet been subjected to economic evaluation. Methods: Incremental cost-effectiveness analysis was undertaken from the health service provider perspective, over the period of hospitalization (time horizon) using the Australian Dollar (A$) at 2008 values. Analyses were based on data from a randomized trial among n = 1,206 acute and rehabilitation inpatients. Decision tree modeling with three-way sensitivity analyses were conducted using burden of disease estimates developed from trial data and previous research. The intervention was a multimedia patient education program provided with trained health professional follow-up shown to reduce falls among cognitively intact hospital patients.Results: The short-term cost to a health service of one cognitively intact patient being a faller could be as high as A$14,591 (2008). The education program cost A$526 (2008) to prevent one cognitively intact patient becoming a faller and A$294 (2008) to prevent one fall based on primary trial data. These estimates were unstable due to high variability in the hospital costs accrued by individual patients involved in the trial. There was a 52% probability the complete program was both more effective and less costly (from the health service perspective) than providing usual care alone. Decision tree modeling sensitivity analyses identified that when provided in real life contexts, the program would be both more effective in preventing falls among cognitively intact inpatients and cost saving where the proportion of these patients who would otherwise fall under usual care conditions is at least 4.0%. Conclusions: This economic evaluation was designed to assist health care providers decide in what circumstances this intervention should be provided. If the proportion of cognitively intact patients falling on a ward under usual care conditions is 4% or greater, then provision of the complete program in addition to usual care will likely both prevent falls and reduce costs for a health service.